Mainsprings of the German revival - Wallich, Henry Christopher (Westport, Conn. : Greenwood Press, 1976)
This book tries to discover the mainsprings that gave the revival of western Germany momentum.
Reprint of the ed. published by Yale University Press, New Haven, which was issued as no. 5 of Yale studies in economics.
Includes bibliographical references and index.
aia 10/05/2018
Loans
Keywords: Germany (West) -- Economic conditions; Germany (West) -- Economic policy; Germany (West).